Global analysis of lysine 2-hydroxyisobutyrylation during Fusarium graminearum infection in maize - Zhang, Kang; Cao, Hongzhe; Ma, Yuxin; Si, Helong; Zang, Jinping; Bai, Hua; Yu, Lu; Pang, Xi; Zhou, Fan; Xing, Jihong; Dong, Jingao (Frontiers in Plant Science, 2022)
Proteins post-translational modification (PTMs) is necessary in the whole life process of organisms. Among them, lysine 2-hydroxyisobutyrylation (Khib) plays an important role in protein synthesis, transcriptional regulation, and cell metabolism. Khib is a newly identified PTM in several plant species. However, the function of Khib in maize was unclear. In this study, western blotting results showed that Khib modification level increased significantly after Fusarium graminearum infection, and 2,066 Khib modified sites on 728 proteins were identified in maize, among which 24 Khib sites occurred on core histones. Subcellular localization results showed that these Khib modified proteins were localized in cytoplasm, chloroplast, and nucleus. Then, comparative proteomic analysis of the defense response to F. graminearum infection showed that Khib modification participated in plant resistance to pathogen infection by regulating glycolysis, TCA cycle, protein synthesis, peroxisome, and secondary metabolic processes, such as benzoxazinoid biosynthesis, phenylpropanoid biosynthesis, jasmonic acid synthesis, and tyrosine and tryptophan biosynthesis. In addition, we also demonstrated that lysine 2-hydroxyisobutyrylation sites on histones were involved in the gene expression of pathogenesis-related proteins. Our results provide a new perspective for the study of plant disease resistance, and had directive significance of maize disease resistance for molecular breeding.